Risk factors for linezolid-associated hyponatremia focused on differences between intravenous and oral administration: a single-center, retrospective study - Ryoji Takata; Masatoshi Taga; Hirofumi Nagai; Yoshihiro Nishita; Hironori Kobayashi; Nozomi Arakawa; Toru Imai; Yoshitsugu Iinuma; Togen Masauji (Journal of Pharmaceutical Health Care and Sciences)
Abstract Background Linezolid (LZD)-associated hyponatremia is a rare side effect, and no reports have compared intravenous and oral administration in relation to the development of hyponatremia. This study aimed to identify risk factors for LZD-associated hyponatremia and to evaluate whether there are differences in the development of hyponatremia between intravenous and oral administration. Methods We conducted a retrospective study that included patients aged ≥ 20 years who received LZD of 1200 mg/day intravenously or orally at Kanazawa Medical University Hospital from January 2011 to December 2023. Patient information was retrospectively examined, and multiple logistic regression analysis was used to assess the risk of intravenous administration for hyponatremia. Additionally, propensity scores were calculated for the intravenous and oral administration groups, and these scores were subsequently used in a propensity score matching analysis. Results This retrospective study revealed hyponatremia in 32 of 240 (13.3%) patients. Intravenous administration (OR = 17.137, 95% CI = 2.029–144.712, P = 0.009), serum sodium level before administration (OR = 0.626, 95% CI = 0.528–0.744, P < 0.001), and creatinine clearance (OR = 0.987, 95% CI = 0.975–0.999, P = 0.040) were identified as independent variables associated with hyponatremia. After propensity score matching, the incidence of LZD-associated hyponatremia was higher with intravenous administration than with oral administration (OR = 9.697, 95% CI = 1.153–81.545, P = 0.029). Conclusions This study identified intravenous administration as an independent risk factor for LZD-associated hyponatremia, and that the risk of hyponatremia was significantly higher with the intravenous administration compared with the oral administration. Patients with the identified risk factors should be administered intravenous LZD more cautiously and carefully monitored for serum sodium levels.